Cleft Lip and Palate Research in Low- and Middle-income Countries: A Scientometric Analysis. Issue 2 (15th February 2022) - Kanmounye, Ulrick Sidney; Dutton, John L.; Naidu, Priyanka; Msokera, Chifundo; Collier, Zachary J.; Fernanda Tapia, Maria; Mikhail, Shady; Xepoleas, Meredith; Auslander, Allyn; Yao, Caroline A.; Magee, William
Abstract : Background: Cleft lip and palate (CLP) comprise over 90% of the world's congenital anomalies and cause significant disability worldwide, while disproportionally burdening low- and middle-income countries (LMICs). Research can help inform strategies that reduce disparities in accessing CLP care. We performed a scientometric analysis of CLP research in LMICs to identify influential contributors and themes. Methods: The authors searched seven citation databases accessed via Web of Science, from inception to March 2, 2021. Social network analysis was done using VOSviewer. The Kruskal-Wallis test and linear regression were used. Results: In total, 1561 articles authored by 6414 researchers affiliated with 2113 organizations in 119 countries were included. Most authors (n = 6387, 99.6%) had published two or more articles. The USA (454 articles), Brazil (211 articles), China (175 articles), and India (127 articles) published the most. The most prolific institutions were the University of Sao Paulo (94 articles), the University of Pittsburgh (57 articles), and the University of Iowa (55 articles). Marazita ML (33 articles), Shi B (27 articles), and Murray JC (22 articles) had the highest number of publications. An estimated 510 articles (32.7%) were focused on epidemiology, 240 (15.4%) on management, and 54 (3.5%) on global plastic surgery for CLP. Conclusions: LMICs are disproportionally burdened by CLP, but research is limited and often produced by high-income countries. This study elucidates partnership and health system strengthening opportunities to improve LMIC research capacity and ultimately informs the management and outcomes for patients with CLP.